1981
DOI: 10.1083/jcb.88.2.338
|View full text |Cite
|
Sign up to set email alerts
|

Density and distribution of α-bungarotoxin-binding sites in postsynaptic structures of regenerated rat skeletal muscle

Abstract: Acetylcholine receptors (AChR) are organized in a discrete and predictable fashion in the postsynaptic regions of vertebrate skeletal muscle . When muscle is damaged, nerves and myofibers including muscular elements of the endplate degenerate, but the connective tissue elements survive. Muscle fibers regenerate within the basal lamina of the original myofiber . Postsynaptic differentiation in regenerated mammalian skeletal muscle can occur in different ways : (a) at the site of the original endplate in the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
25
2

Year Published

1982
1982
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 35 publications
6
25
2
Order By: Relevance
“…It appears, therefore, that even at established adult end-plates receptor density and receptor metabolism are not tightly coupled. This is consistent with previous observations that during development receptor aggregation, receptor function and receptor metabolism appear to be independently controlled (Steinbach et al 1979;Fischbach & Schuetze, 1980;Reiness & Weinberg, 1981;Michler & Sakmann, 1980;Steinbach, 1981a (Burden, Sargent & McMahan, 1979;Bader, 1981). It is possible that molecules in the basal lamina, which are removed or modified by collagenase treatment, also play a role in determining the metabolic stability of junctional ACh receptors; these molecules may be sensitive to enzymes released at end-plates after denervation.…”
Section: Discussionsupporting
confidence: 80%
“…It appears, therefore, that even at established adult end-plates receptor density and receptor metabolism are not tightly coupled. This is consistent with previous observations that during development receptor aggregation, receptor function and receptor metabolism appear to be independently controlled (Steinbach et al 1979;Fischbach & Schuetze, 1980;Reiness & Weinberg, 1981;Michler & Sakmann, 1980;Steinbach, 1981a (Burden, Sargent & McMahan, 1979;Bader, 1981). It is possible that molecules in the basal lamina, which are removed or modified by collagenase treatment, also play a role in determining the metabolic stability of junctional ACh receptors; these molecules may be sensitive to enzymes released at end-plates after denervation.…”
Section: Discussionsupporting
confidence: 80%
“…Despite these uncertainties, however, the firm conclusion from our experiments is that all five proteins studied are components of muscle fiber basement membrane and are closely associated with the basal lamina . Our interest in comparing synaptic and extrasynaptic basement membrane stems from the fording that the synaptic region is functionally specialized : When new neuromuscular junctions form following injury, regenerating axons preferentially contact original synaptic sites on the basement membrane and differentiate into nerve terminals at these sites in the absence ofthe muscle fiber (36); acetylcholine receptors on regenerating myotubes cluster at original synaptic sites on the basement membrane in the absence of the nerve (1,5). In addition, acetylcholinesterase, which terminates neurotransmitter action at the neuromuscular junction, is connected to or contained in synaptic basement membrane (19,28), and adhesion of nerve to muscle at the neuromuscular junction may be mediated by components of synaptic basement membrane (2,36).…”
Section: Discussionmentioning
confidence: 99%
“…A small fraction of the basement membrane, -0.1% of the total, occupies the synaptic cleft between nerve and muscle at the neuromuscular junction. Recent experiments have demonstrated that this synaptic portion of the basement membrane is specialized and plays important roles in neuromuscular function and regeneration (1,2,5,19,28,36) . These results motivate molecular analysis of muscle-fiber basement membrane and comparison of its synaptic and extrasynaptic portions.…”
mentioning
confidence: 99%
“…The top ~2,000 A of postjunctional membrane (pjm) has a distinct electron density, a cytoplasmic filamentous substructure (4) and is rich in intramembrane particles (13,26,28). This thickened region has a high density of receptors (~10,000-20,000 sites/#m 2) (2,15,16, 19,23,27). At the bottom of the folds, the membrane is morphologically indistinguishable from that at extrajunctional regions, and the receptor site density is considerably reduced (~ 1,000 sites//.tm 2, or ~5-10% the site density at the top of the folds).…”
mentioning
confidence: 99%